Correction: The effect of public reporting of acute myocardial infarction on the choice of hospital - Kim, Mira; Lee, Kyungshin; Chae, Kyunghee; Jung, Chai-Young; Lee, Sangmin; Quan, Hude; Kim, Sukil (PloS one, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0323780.].